PEMIKIRAN RELIGIUS-RASIONAL H. M. ARIFIN DAN RELEVANSINYA DENGAN PENDIDIKAN ISLAM MODERN - Muammar Zulfiqri; Sutan Akhyar Rajabi (Universitas Islam Depok, 2024)
This article discusses the figure of H. M. Arifin M.Ed.The purpose of this article is to get to know the figure of H. M. Arifin, as well as analyze his thoughts on Islamic education and its suitability with modern Islamic education. The method used in this paper is a library research method, using a pragmatic approach. The data sources are collected from books and journals, and analyze it using descriptive steps. The research result show that H.M.Arifin is an academic with a qualified educational background and his career is as a researcher and lecturer. H. M. Arifin’ss thoughts include aspects of goals, curriculum, methods, evaluation and educational institutions, which as a whole refers to the goal of the Islamic religion itself, namely obtaining happiness in this word and the afterlife. His thoughts are in line with modern Islamic education which requires students to have skills, intellect and a religious spirit.